Integrated management of on-site, coordination and off-site uncertainty: Theorizing risk analysis within a hybrid project setting. Issue 4 (May 2017) - Arashpour, Mehrdad; Abbasi, Babak; Arashpour, Mohammadreza; Reza Hosseini, M.; Yang, Rebecca
Abstract: Hybrid infrastructure projects are defined as triads of on-site/coordination/off-site project dimensions. Interaction of uncertainties in such settings result in deviations from project objectives by causing time and cost overruns, safety issues, quality deficiencies, technical problems, and lack of client satisfaction. To address these, a holistic approach in identifying and analyzing risks in hybrid (multi-dimensional) projects is proposed. Towards this aim, three research hypotheses are developed and tested using data from seven projects in Melbourne, Perth and Adelaide, Australia. Practical implications of triadic risk analysis in hybrid infrastructure projects suggest executives and managers to put more emphasis on risks associated with coordination of on-site and off-site project dimensions. This approach significantly decreases the chance of deviations from project objectives. Highlights: In a dyadic risk analysis, off-site uncertainty has higher impact on project objectives than on-site uncertainty. The average probability of occurrence for on-site risks is more than off-site risks. In hybrid projects as on-site/coordination/off-site triads, coordination risks cause significant deviation from objectives.